Data fusion of multimodal cardiovascular signals for clinical diagnosis - Boindala Madhu Bindu. (2008)
To apply advanced signal processing techniques to cardiovascular, respiratory, arterial blood pressure system signals, to extract significant features and to perform relevant analysis to obtain meaningful information for clinical diagnosis.